ISOLASI DAN UJI AKTIVITAS BAKTERI ASIDOFILIK PENGOKSIDASI BESI DAN SULFUR DAR! EKOSISTEM AIR HITAM DI KALIMANTAN TENGAH - Nurseha Nurseha; Gunawan Djajakirana (Jurnal Ilmu Tanah dan Lingkungan, 2004)
The acidophilic iron and sulfur-oxidizing bacteria were isolated from the black water ecosystem, an 'extreme' ecosystem affected indirectly or directly by peatland Isolation and selection were done on minimal media (liquid and solid). All selected strain of bacteria (BB 179, OM 349, AH 41, TB 23, TB 27, TP 3, NN 323, and SI 188) were identified as Thiobacillus ferrooxidans. Biooxidation and bio-leaching tests were accomplished using the isolated bacteria. The results showed the capability of the isolated bacteria to oxidize ferrous-salt and to leach the low qualities of sulfide ores. Keywords: Acidophilic, bioleaching, biooxidation, Thiobacillus ferrooxidans